Inferring the Contribution of Microbial Taxa and Organic Matter Molecular Formulas to Ecological Assembly - Danczak, Robert E.; Sengupta, Aditi; Fansler, Sarah J.; Chu, Rosalie K.; Garayburu-Caruso, Vanessa A.; Renteria, Lupita; Toyoda, Jason; Wells, Jacqueline; Stegen, James C. (Frontiers in Microbiology, 2022)
Understanding the mechanisms underlying the assembly of communities has long been the goal of many ecological studies. While several studies have evaluated community wide ecological assembly, fewer have focused on investigating the impacts of individual members within a community or assemblage on ecological assembly. Here, we adapted a previous null model (βNTI) to measure the contribution of individual features within an ecological community to overall assembly. This new metric, called feature-level βNTI (βNTIfeat), enables researchers to determine whether ecological features (e.g., individual microbial taxa) contribute to divergence, convergence, or have insignificant impacts across spatiotemporally resolved metacommunities or meta-assemblages. Using βNTIfeat, we revealed that unclassified microbial lineages often contributed to community divergence while diverse groups (e.g., Crenarchaeota, Alphaproteobacteria, Gammaproteobacteria) contributed to convergence. We also demonstrate that βNTIfeat can be extended to other ecological assemblages such as organic molecules comprising organic matter (OM) pools. OM had more inconsistent trends compared to the microbial community though CHO-containing molecular formulas often contributed to convergence while nitrogen and phosphorus-containing formulas contributed to both convergence and divergence. A network analysis was used to relate βNTIfeat values from the putatively active microbial community and the OM assemblage and examine potentially common contributions to ecological assembly across different communities/assemblages. This analysis revealed that P-containing formulas often contributed to convergence/divergence separately from other ecological features and N-containing formulas often contributed to assembly in coordination with microorganisms. Additionally, members of Family Geobacteraceae were often observed to contribute to convergence/divergence in conjunction with both N- and P-containing formulas, suggesting a coordinated ecological role for family members and the nitrogen/phosphorus cycle. Overall, we show that βNTIfeat offers opportunities to investigate the community or assemblage members which shape the phylogenetic or functional landscape, and demonstrate the potential to evaluate potential points of coordination across various community types.